High-Dose Vitamin C Alleviates Pancreatic Necrosis by Inhibiting Platelet Activation Through the CXCL12/CXCR4 Pathway in Severe Acute Pancreatitis - Gui M; Huang J; Sheng H; Chen Y; Yang Z; Ma L; Wang D; Xu L; Sun W; Liu J; Xu Y; Chen E; et al. (Dove Medical Press, 2023)
Menglu Gui,1,* Jun Huang,2,* Huiqiu Sheng,1,* Ying Chen,1 Zhitao Yang,1 Li Ma,1 Daosheng Wang,3 Lili Xu,1 Wenwu Sun,1 Junling Liu,4 Yanyan Xu,4 Erzhen Chen,1 Bing Zhao,1 Enqiang Mao1 1Department of Emergency in Ruijin Hospital Affiliated to Shanghai Jiao Tong University School of Medicine, Shanghai, 200025, People's Republic of China; 2Department of Cardiovascular Medicine, State Key Laboratory of Medical Genomics, Shanghai Key Laboratory of Hypertension, Shanghai Institute of Hypertension, Ruijin Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, 200025, People's Republic of China; 3Department of Laboratory Medicine in Ruijin Hospital Affiliated to Shanghai Jiao Tong University School of Medicine, Shanghai, 200025, People's Republic of China; 4Department of Biochemistry and Molecular Cell Biology, Key Laboratory of Cell Differentiation and Apoptosis of Chinese Ministry of Education, Shanghai Jiao Tong University School of Medicine, Shanghai, 200025, People's Republic of China*These authors contributed equally to this workCorrespondence: Enqiang Mao; Bing Zhao, Department of Emergency in Ruijin Hospital Affiliated to Shanghai Jiao Tong University School of Medicine, Shanghai, 200025, People's Republic of China, Tel +8613501747906 ; +8618017117871, Email maoeq@yeah.net; zhaobing124@163.comBackground: Platelet activation in the early stage of pancreatitis is the key step developing into pancreatic necrosis. Studies suggested that vitamin C (Vit C) can inhibit platelet activity by targeting CXCL12/CXCR4 pathway. High-dose Vit C were showed to reduce pancreatic necrosis in severe acute pancreatitis (SAP) but the mechanism remains unclear. Here we speculate high-dose Vit C reduce pancreatic necrosis by inhibiting platelet activation through downregulating CXCL12/CXCR4 pathway.Methods: The pancreatic microcirculation of rats was observed by intravital microscopy. The platelet activity of SAP rats treated with or without high-dose Vit C was analyzed by platelet function test. Besides, the activity of platelets preincubated with high-dose Vit C or vehicle from SAP patients was also evaluated. Then, the TFA (CXCR4 agonist) and rCXCL12 were used to neutralize the effect of high-dose Vit C in SAP rats treated with high-dose Vit C. Meanwhile, the levels of enzymes and inflammatory cytokines in rat plasma, and rats' pancreatic histopathology and mortality were assessed.Results: Platelets from animals and patients with SAP are more sensitive to agonists and are more easily activated. Administration of high-dose Vit C significantly ameliorated excessive activation of platelets in SAP rats, ultimately increasing the microvessel density and inducing microthrombus and blood stasis; these results were consistent with clinical sample analysis. Moreover, high-dose Vit C significantly inhibited the release of amylase, lipase, TNF-α, and IL-6 in SAP rat plasma, reducing pancreatic damage and the mortality of SAP rats. However, using TFA and rCXCL12 significantly reversed the effect of high-dose Vit C on excessive activation of platelets, aggravating microcirculation impairment and pancreatic damage.Conclusion: The present study suggests that high-dose Vit C can ameliorate pancreatic necrosis by improving microcirculation disorders of SAP. For the first time, the underlying mechanism is related with inhibiting platelet activation through the CXCL12/CXCR4 pathway.Keywords: severe acute pancreatitis, microcirculation impairment, platelets activity, vitamin C, CXCL12/CXCR4 pathway